ON THE CORRELATION OF IR AND OPTICAL VARIABILITYIN NGC 4151 - Oknyanskij, V. L.; Lyuty, V. M.; Taranova, O. G.; Koptelova, E. A.; Shenavrin, V. I. (Одеські астрономічні публікації, 2008)
We combine all published and new unpublished yet NIR (near infrared) photometrical observations of NGC 4151 which can be used for determination of time delays between optical and NIR variations. In previous study we have found that the values of time delay in NIR filters are not the same for different states of the luminosity. Here we consider the new photometrical data for the deep minimum in 2003-2007 following the very high state of the nucleus. We conclude that after sublimation in high state of nucleus the dust particles were recovering during at least several years.